2022
DOI: 10.1002/bkcs.12485
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory in classical explicit solvents: Mean‐field QM/MM method for simulating solid–liquid interfaces

Abstract: Solid-liquid interfaces are ubiquitous in scientifically and technologically important systems, and they govern complex chemophysical processes such as those in electrochemistry and heterogeneous catalysis. Atomic-level elucidation of interfacial structures has been extensively pursued; however, related research is still limited. A major obstacle lies in the intrinsic character of interfaces: they are located between two bulk phases that make the application of spectroscopic or surface-science techniques be di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…To identify the chemical role of M + during CO 2 RR, we first investigate atomic details of the catalyst–electrolyte interface using density functional theory in classical explicit solvent (DFT-CES) simulation 36 . This method offers an accurate description of the electrified interface at a balanced computational cost, by mean-field coupling of a quantum mechanical description on the catalyst surface with a molecular dynamics description on the liquid structure of the electrolyte phase 37 . Recent advances in computational simulations enable a direct investigation of the electrode-electrolyte structure, highlighting the importance of the atomic arrangement of EDL constituents (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…To identify the chemical role of M + during CO 2 RR, we first investigate atomic details of the catalyst–electrolyte interface using density functional theory in classical explicit solvent (DFT-CES) simulation 36 . This method offers an accurate description of the electrified interface at a balanced computational cost, by mean-field coupling of a quantum mechanical description on the catalyst surface with a molecular dynamics description on the liquid structure of the electrolyte phase 37 . Recent advances in computational simulations enable a direct investigation of the electrode-electrolyte structure, highlighting the importance of the atomic arrangement of EDL constituents (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…DFT-CES is a grid-based mean-field QM/MM method that was recently developed by the Kim group [ 26 , 27 , 28 ]. The mean-field QM/MM method iteratively solves QM optimizations and molecular dynamics (MD) simulations until a self-consistent solution is obtained [ 29 , 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Assuming that the solvation effect’s presence is a major distinction between the inter-residue interactions of folded proteins and IDPs, we explored aromatic π–π interactions in aqueous environments. We examined how water solvation modifies the π–π interaction of benzene and phenol dimers by combining two modern computational chemistry methods: (1) the van der Waals (vdW)-corrected density functional theory (DFT) for an accurate description of direct monomer–monomer interaction energy; (2) DFT in classical explicit solvents (DFT-CES), which is a mean-field quantum mechanics/molecular mechanics (QM/MM) method [ 26 , 27 , 28 ] enabling an explicit treatment of solvent molecules for a reliable description of solvation free energy. We found that the solvation effect renormalizes the interaction energies between benzene and phenol molecules, the conformational dependence of which can be understood in terms of the changes in the number of hydrogen bonds (HB) before and after dimer formation: water–benzene HB for benzene dimers and water–hydroxyl HB for phenol dimers.…”
Section: Introductionmentioning
confidence: 99%
“…In this section, a brief discussion is presented on the various features of the biosensors and drug delivery systems, that can be predicted using quantum chemical methods. Density functional theory (DFT) ranks as the most widely used quantum mechanical method and plays an increasingly larger role in a number of disciplines besides chemistry, such as physics, materials, biology, and pharmacy [94][95][96][97][98][99][100][101][102][103]. While DFT computations have long been used to complement experimental investigations, the approach has emerged as an indispensable and powerful tool for predictions of different fields.…”
Section: Methodsmentioning
confidence: 99%